Genealogi Pendidikan Pesantren sebagai Pembentuk Tradisi Islam di Indonesia: Genealogy of Pesantren Education as the Shaper of Islamic Traditions in Indonesia - Hasanah, Atin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2021)
This paper aims to explain the genealogy of pesantren in shaping Islamic traditions in Indonesia. Pesantren has a characteristic that is obtained through the creative translation of the heritage of Western and Middle Eastern traditions. The type of research used is a qualitative literature study model with a social history approach. The research theory uses post-colonial Edward Said. The results showed; First, the scientific roots of pesantren are Islam during the Walisongo period. Second, Islamic boarding school education has become stable and established due to the emergence of the nation-state century. Third, there are two types of cultural brokers from pesantren, namely pesantren and Kiai figures.